Efficacy and safety of vitamin E as adjunctive therapy for epilepsy: a systematic review and meta-analysis of randomized control trials - Yanfei Li; Yanfei Li; Gefei He; Gefei He; Juanjuan Huang; Juanjuan Huang; Lin Hu; Lin Hu (Frontiers in Neurology)
ObjectiveVitamin E, functioning as an antioxidant, holds substantial potential in the adjuvant treatment of epilepsy. However, it remains uncertain whether the existing evidence is adequate to validate the use of vitamin E as an add-on therapy for improving epilepsy outcomes. The aim of this study was to explore the efficacy and safety of vitamin E as an adjuvant treatment for epilepsy.MethodsWe searched PubMed, Embase, the Cochrane Library, and Chinese databases including the Chinese Biomedicine Literature Database, China National Knowledge Infrastructure, Chinese Sci-tech Journal Database, Wanfang Data for eligible studies from inception to February 28, 2025. Meta-analysis was performed to calculate the risk ratio (RR) and weighted mean difference (WMD) of the included randomized controlled trials (RCTs).ResultsAmong the 2,348 records obtained, 11 RCTs involving 824 patients were included after literature screening. Vitamin E had a potential advantage in reducing seizure frequency by >75% (RR = 1.73, 95% confidence interval (CI) (1.31, 2.28), p < 0.01), compared with the control group. Subgroup analysis showed a statistically significant difference in the reduction of seizure frequency by >50% (RR = 1.58, 95% CI (1.27, 1.96), p < 0.01) between the vitamin E group and the control group, especially in children (RR = 1.69, 95% CI (1.29, 2.20), p < 0.01). The plasma total antioxidant capacity was higher (WMD = 3.03, 95% CI (2.65, 3.40), p < 0.01) while the malondialdehyde levels were lower (WMD = −6.28, 95% CI (−8.01, −4.54), p < 0.01) in the vitamin E group than in the control group. There was no statistically significant difference in the rates of total adverse events (RR = 0.97, 95% CI (0.93, 1.02), p = 0.25).ConclusionVitamin E shows potential as adjunctive therapy, particularly in pediatric populations, with acceptable safety profile, but high-quality trials are required to confirm its efficacy and safety.